Genetic Variability Of Some Cytoplasmic Male Sterile Lines (CMS) Of Rice (Oryza Sativa L.) Genotypes (Bangladesh Journal of Agricultural Research, 2011)
The desirable characteristics of fourteen genetically diverse CMS lines were assessed for their phenotypic acceptability, plant height (cm), days to 50% flowering. panicles per plant, stability for pollen sterility, panicle exertion rate and out crossing rate. The CMS lines viz. BRRI1A. IR 58025A. BRRI10A. BRRI9A. BRRI3A, IR 75608A, and 1132A have been found to be usable female parents for hybrid rice breeding due to their appreciable phenotypic acceptability, stable pollen sterility, panicle exertion rate and good out crossing rate. Panicle exertion rate of CMS lines had moderate heritability (38.34%) coupled with low genetic advance (2.34%) expected in the subsequent generations, that proved to be vulnerable to environmental fluctuation. The genotypic and phenotypic coefficient of variation was not remarkably varied from each other for most of the characters studied, indicated negligible environmental influence on these traits. Overall genetic correlation coefficients were higher than corresponding phenotypic correlation coefficients indicated strong relation present among the studied characters. Keywords: Genetic variability; CMS lines; rice. DOI: http://dx.doi.org/10.3329/bjar.v36i2.9253 BJAR 2011; 36(2): 263-270